Unplanned pregnancy as a social predictor of COVID-19 severity among pregnant women in Yogyakarta: Study of path analysis - Puspitasari, Sepsiana; Hernayanti, Munica Rita; Lamawatu, Nuril F.; Wahyuningsih, Windu Syawalina (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2025)
Introduction: Pandemic Corona Virus Disease-19 (COVID-19) has passed, but social determinants severity of COVID-19 in pregnant women are still under report. Pregnant women have a higher risk of experiencing severe COVID-19 infection, with the potential for serious complications for maternal and fetal health. The impact of pregnancy planning towards severity of COVID-19 in pregnant women is still lack reported. Objective: this study conducted to determine social factors that predict COVID-19 with severe symptoms among pregnant women at Rumah Sakit Lapangan Khusus COVID-19 (RSLKC) in Yogyakarta Province, Indonesia.Method: through the case-control study, 99 pregnant women who had experienced COVID-19 between August 2021 and May 2022 and were treated at RSLKC self-reporting the retrospective data. Chi square test and path analysis were used for determining the relationship and the direction on the dependent variable, respectively.Results: severe symptoms of COVID-19 were experienced by pregnant who were not vaccinated (p=0.032), undergo daily physical work (p = 0.023) and undergo unplanned pregnancy (p=0.027). The three variables have a direct influence coefficient magnitude -2.62; 4.05; 2.12, respectively. Unplanned pregnancy is directly influenced by age >35 years and the number of children with coefficient magnitudes 2.81.; -1.69, respectively.Conclusion: Unplanned pregnancy is a potential social determinant of severe COVID-19 symptoms in pregnant women and other several factors such as vaccine status and physical work (as direct factors), as well as age > 35 years and number of children (as indirect factors that predict unplanned pregnancy).